Gender and practice : insights from the field - Demos, Vasilikie; Segal, Marcia Texler; Kelly, Kristy (Advances in gender research ;, 2019)
UN Sustainable Development Goal 5: Achieve Gender Equality and Empower All Women and Girls.In Gender and Practice: Insights from the Field, twelve chapters contribute to the creation of an accessible body of knowledge that looks to provide gender practitioners with examples of what works, and what doesn't, in the attainment of gender equality.This volume demonstrates the depth and breadth of gender and practice. Looking across countries including Cambodia, India, Kazakhstan, Tanzania, Uganda, Vietnam, and the United States, the chapters explore global perspectives and global ramifications. Contributors examine issues and activities related to infusing gender in education, training and practice, and many chapters specifically address one or more of the UN Sustainable Development Goals. Including chapters on medical treatment, climate change, non-profit and community organizing, and agriculture, this volume is useful to all those looking to explore current gender research.